2020
DOI: 10.1136/gutjnl-2020-322780
|View full text |Cite
|
Sign up to set email alerts
|

F. nucleatum targets lncRNA ENO1-IT1 to promote glycolysis and oncogenesis in colorectal cancer

Abstract: ObjectiveMicrobiota disorder promotes chronic inflammation and carcinogenesis. High glycolysis is associated with poor prognosis in patients with colorectal cancer (CRC). However, the potential correlation between the gut microbiota and glucose metabolism is unknown in CRC.Design18F-FDG (18F-fluorodeoxyglucose) PET (positron emission tomography)/CT image scanning data and microbiota PCR analysis were performed to measure the correlation between metabolic alterations and microbiota disorder in 33 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 49 publications
0
126
0
2
Order By: Relevance
“…Previously, Hong et al (2020) reported histone acetylation of specific genes following Fn-induced lncRNA ENO1-IT upregulation. To our knowledge, our present study is the first to explore epigenome-wide changes in host chromatin in response to Fn exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, Hong et al (2020) reported histone acetylation of specific genes following Fn-induced lncRNA ENO1-IT upregulation. To our knowledge, our present study is the first to explore epigenome-wide changes in host chromatin in response to Fn exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Upregulated ENO1-IT activates the target genes including ENO1, resulting in elevated glycolysis and enhanced tumor growth. 147 HIF-1α induces upregulation of lncRNA AC020978 in NSCLC. Elevated AC020978 stabilizes PKM2 by protecting it from degradation.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Upregulated ENO1-IT activates the target genes including ENO1, resulting in elevated glycolysis and enhanced tumor growth. 147 …”
Section: Deregulated Mechanisms Of Lncrnas In Cancer Glycolysismentioning
confidence: 99%
“…Interestingly, even microorganisms may modify glucose metabolism in cancer via lncRNAs. Fusobacterium nucleatum, a member of the normal flora in the oral cavity, activates lncRNA ENO1-IT1 transcription that eventually induces glucose metabolism in colorectal cancer (CRC) [30].…”
Section: Lncrnas Regulates Pathophysiological Processes In Cancer Via the Influence Of Glucose Metabolismmentioning
confidence: 99%